Genetic variability and correlation studies in backcross inbred lines of rice in direct seeded aerobic conditions - M. Arivin; K. R. Saravanan; P. Senguttuvel; N. Senthilkumar; K. K. Raghuraman; B. Sunilkumar; P. Thangavel (The Bioscan, 2025)
The research was conducted to evaluate the genetic variability parameters and correlation analysis for ten yield-related traits of stabilized Backcross Inbred Lines (BILs), derived from an aerobic restorer AR-9-18 and YPK 198 under direct seeded aerobic conditions at ICAR-IIRR, Hyderabad during kharif 2022. The results indicated that the productive tiller number showed high PCV and GCV. Productive tiller number, primary branches, grain number per panicle, test grain weight, grain weight per panicle and plant yield exhibited a high heritability and also high genetic advance as per cent of mean which demonstrates simple selection would be effective for improvements of these traits. Correlation studies indicated that plant yield was associated significantly positive with productive tiller number, days to 50 percent flowering, and test grain weight.